The utilization of soybean straw III: Isolation and characterization of lignin from soybean straw. (November 2016) - Liu, Zhulan; Meng, Lingkun; Chen, Junqing; Cao, Yunfeng; Wang, Zhiguo; Ren, Hao
Abstract: To improve the yield of cellulolytic enzyme lignin (CEL) and to minimize the structural changes induced by isolation, the dissolution-regeneration of ball-milled soybean stem in a lithium chloride (LiCl)/dimethyl sulfoxide (DMSO) solvent was applied prior to enzymatic hydrolysis. The regenerated stem was enzymatically hydrolyzed for 72 h to remove the carbohydrates and then extracted with 1, 4-dioxane to obtain the cellulolytic enzyme lignin (named as DR-CEL). As expected, the yield of DR-CEL was much higher than that of CEL. With 2 h of ball-milling, the yield of DR-CEL was 40.1% (based on the total lignin in the raw stem). As the ball-milling time increased to 4 h, the yield of DR-CEL improved up to 82.4%, which was much higher than that of CEL with a yield of 26.0%. All the isolated lignin preparations were characterized using FT-IR, 1 H NMR and 1 H- 13 C HSQC NMR. The results showed that the main structural characteristics of these two kinds of lignin (CEL & DR-CEL) were similar, except for a slightly higher amount of carbohydrates in DR-CEL. As a result, the combination of the dissolution–regeneration and enzyme hydrolysis of ball-milled sample has a great potential in isolating lignin with higher yield and minimal structural changes. Highlights: CEL isolating efficiency was improved by combining dissolution-regeneration with enzymatic hydrolysis. The yield of lignin was greatly improved from 26.0% to 82.5%. There was not too much structural alternation induced by this superior and promising isolating method.